Effectiveness of using the trap barrier system to control rats in palm oil plantations - EFRIANSYAH EFRIANSYAH; SWASTIKO PRIYAMBODO; DADAN HINDAYANA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Efriansyah, Priyambodo S, Hindayana D. 2024. Effectiveness of using the trap barrier system to control rats in palm oil plantations. Biodiversitas 25: 2993-2998. Oil palm is one of the plantation crops that is the largest contributor to the country's income; increased market demand affects palm oil production, which continues to increase. Rats are among the most important pests in oil palm plantations because of their diverse habitats, large populations, and easy breeding. One of the mechanical control concepts that can be implemented is the Trap Barrier System (TBS) technique. This research method was implemented by installing a trap barrier between oil palm trees. This TBS research is divided into two methods. The first method used three treatments with three replications in the main plot, and there were three main plots. The second method used nine treatment sub-plots with three replications. The Ciliwung variety of rice was planted inside the TBS in a 3 m x 3 m plot. Field observations included the number of rats caught and the percentage of damage done at the trial's beginning and end. Species of rats found in oil palm plantations are Malaysian field rat (Rattus tiomanicus Miller, 1900), oriental house rat (Rattus tanezumi Temminck, 1845), and dan müller's giant sunda rat (Sundamys muelleri Jentink, 1879). The S. muelleri was the most frequently caught species in each block and method. TBS placement does not need to pay attention to the initial severity of the block. Providing additional bait in traps can increase the attraction of rats to TBS. The extent and intensity of attacks and yield losses in each block with TBS treatment showed a greater reduction than in blocks without TBS.